Эффективность баннерной интернет-рекламы - Пенькова, И.В.; Усова, А.А. (Культура народов Причерноморья, 2014)
В статье исследованы основные подходы к определению эффективности баннерной
интернет-рекламы. Изучены базовые показатели рентабельности кампании в Интернет. Проведен
анализ рынка интернет-рекламы и количества пользователей в российском его сегменте. Доказано, что
баннерные кампании могут быть эффективными. Обосновано, что баннерную рекламу не рационально
выбирать в качестве основного или единственного вида продвижения. У статті досліджені основні підходи до визначення ефективності банерної інтернет-
реклами. Вивчені базові показники рентабельності кампанії в Інтернет. Проведений аналіз ринку
інтернет-реклами і кількості користувачів в російському його сегменті. Доведено, що банерні кампанії
можуть бути ефективними. Обґрунтовано, що банерну рекламу не раціонально вибирати в якості
основного або єдиного виду просування. In the article there have been investigated the basic approaches to the determination of banner
advertising efficiency. The basic indexes of the Internet campaign profitability have been studied. It is proven
that advertising and exchange networks continue to extend possibilities of audience targeting and offer the cost
for a result. It stipulates loyalty of marketing specialists to the banner model of advertisement. There has been
analyzed the internet-advertising market and quantity of users in its Russian segment. Non-typical users are
subject to the banner advertisement, and it is difficult to be oriented to clickers at the estimation of advertising
campaign. Clickers are ineffective means of measuring and lead to the mistaken evaluation of advertising
campaign efficiency in the Internet. The problem of Russian audience consists in its heterogeneity. There have
been found the principal differences at the consideration of different categories of sites users’ behavior.
Researches in different countries show, that the banner advertisement can positively influence the users’
behavior. It is argued, that banner campaigns can be effective. It is not reasonable to choose banner
advertisement as a basic or the only way of expansion.